Women of valor : Orthodox Jewish troll fighters, crime writers, and rock stars in contemporary literature and culture - Skinazi, Karen E., 1974- (New Brunswick, New Jersey : Rutgers University Press, 2018)
Media portrayals of Orthodox Jewish women frequently depict powerless, silent individuals who are at best naive to live an Orthodox lifestyle, and who are at worst, coerced into it. Skinazi delves beyond this stereotype to identify a powerful tradition of Jewish women's feminist portrayals of Orthodox women in literature, film, and music.
An unorthodox guide to Orthodox Judaism -- A woman of valor (Proverbs 31:10-31) -- Introduction : she puts her hand to the distaff -- A G-d-fearing woman, she should be praised : exposure, dialogue, and remedy in "Off-the-Derech" narratives -- A woman of valor who can find : crime fiction as primers of Orthodoxy -- She opens her mouth with wisdom : this bridge called my voice -- She senses that her enterprise is good : representations of Orthodox businesswomen -- She will be praised at the gates by her very own deeds : the Orthodox artist and the fruit of her hands -- Coda : many daughters have attained valor.
Includes bibliographical references (pages 227-268) and index.
Description based on print version record.
In English.
JSTOR
Keywords: Jewish women -- Religious life; Jewish women in popular culture; Orthodox Judaism; Popular culture -- Religious aspects -- Judaism; Juives -- Vie religieuse; Judaïsme orthodoxe; Culture populaire -- Aspect religieux -- Judaïsme.; RELIGION -- General; Jewish women in popular culture; Jewish women -- Religious life; Orthodox Judaism; Popular culture -- Religious aspects -- Judaism; Electronic books